P367 Identification of neural responses to human faces using wireless multichannel EEG recordings. Issue 9 (September 2017) - Soto, Vicente; Tyson-Carr, John; Kokmotou, Katerina; Roberts, Hannah; Cook, Stephanie; Fallon, Nicholas; Timo Giesbrecht,; Stancak, Andrej
Abstract : Objectives: Previous neuroimaging studies have shown face-specific neural responses to faces compared to objects. The detection of face-specific brain activation in freely behaving and moving people has yet to be accomplished. The purpose of our research was to identify, using wireless multichannel EEG in freely moving participants, eye movement related potentials (EMRPs) during viewing of human faces. Method: Mobile EEG and eye tracking was recorded from 19 freely moving participants whilst they freely viewed a mock art gallery. Stimuli were presented on 20 printed poster panels displaying positive, negative and neutral valence images. A head-mounted wearable eye-tracker was used to capture real-world video recordings of gaze locations used to synchronize the EEG and eye-tracking time-series. Results: Synchronized EEG and eye-tracking recordings allowed identification of a face-related EMRP component (N185 potential) that was not present whilst participants were viewing non-living objects. Source dipole analysis of the evoked component accounted for the ocular-retinal movement artefact and revealed three additional equivalent current dipoles. In the latency interval from 100 to 300 ms one dipole was located to left extrastriate, one to primary visual cortex and one to the right fusiform gyrus. Discussion: Right fusiform gyrus source activity showed sensitivity towards emotional valence suggesting emotional encoding of faces in the fusiform gyrus at a latency interval between 100 and 300 ms. Conclusion: We demonstrate the feasibility of recording EMRP's in freely behaving individuals in a naturalistic setting. Significance: These results open new possibilities to BCI as well as clinical, developmental, social or marketing research.